Analisis Kualitas Kemasan, Persepsi Harga Dan Citra Merek Terhadap Loyalitas Konsumen Pada Biskuit Oreo : Studi Kasus Di Toko Sarimulya Limbangan Wetan - Hanifah Mahry; Yuniarti Ma’nawiyah; Andi Yulianto; Ari Kristiana; Azizah Indriyani (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
A business actor to maintain its extension in order to enter and attract customers by creating good relationships with customers. Creating a good relationship is the goal of business actors to have loyal customers. The purpose of this study is to examine the effect of packaging quality, price perception and brand image on consumer loyalty of Oreo biscuits. This research includes quantitative research. The population of this study is visitors from May 2023 as many as 564 buyers. The sampling technique used in this study was the Slovin formula with a margin of error of 10% obtained by 85 respondents. The data analysis techniques used are instrument tests, classical assumption tests, multiple regression analysis, and hypothesis testing. The results of this study show that packaging quality has a positive and significant effect on consumer loyalty, price perception has a positive and significant effect on consumer loyalty, brand image has a positive and significant effect on consumer loyalty. Packaging quality, price perception, and brand image simultaneously have a positive and significant effect on consumer loyalty of Oreo products at the Sarimulya Limbangan store.